An Empirical Study of Latitude of Quantity Acceptance (LQA) in an Emerging Economy: India. Issue 2 (15th March 2018) - Saini, Gordhan; Sahay, Arvind; Kalyanaram, Gurumurthy
ABSTRACT: This study examines three important research questions. First, is there a latitude of acceptance with respect to small quantity changes? Second, is there an asymmetric effect of quantity changes? Third, is there a differential effect between high-equity and low-equity brands in response to quantity changes which is acceptable to customers? The effect of quantity change on purchase intention was examined through the decrease (increase) in original quantity of high-equity brands (low-equity brands), keeping price constant. ANOVA and ANCOVA were used to estimate the main and interaction effects. Empirical results show that: (a) there is evidence for LQA; (b) the effect of quantity change is asymmetric; and (c) the LQA range is larger for low-equity brands. A lower range of LQA for high-equity brands limits quantity reduction choice as a firm strategy and lowering price by a small percentage is unlikely to be successful for a low-equity brand.